Correlating nanoscale optoelectronic and mechanical properties of solution processable thin film photovoltaic materials using scanning probe microscopy - Vorpahl, Sarah (My University, 2018)
Solution processable materials present a competitive alternative to traditional silicon solar cells based on inexpensive processing and flexible form factors. Several competing technologies have entered the market in the past few years, including cadmium telluride and copper, indium, gallium, sulfur (CIGS) alloys. In addition to this nascent commercialized product, several emerging technologies also offer promising alternatives. Copper, zinc, tin, sulfur (CZTS) kesterite materials offers an earth abundant option, moving away from more price volatile minerals such as the indium used in CIGS. Hybrid perovskites (HPs) have been revealed as one of the most exciting new solution processable materials, with efficiency improving exponentially in just the past several years. This dissertation explores the underlying electrical and mechanical properties of both CZTS and HP thin films using scanning probe microscopy (SPM). Using several correlated SPM techniques, local functional properties are related to bulk performance as a way to help understand the fundamental properties that drive material characteristics.
Thesis (Ph.D.)--University of Washington, 2017-09
Keywords: atomic force microscopy; CZTS; perovskite; solar cell; solution processable; Energy; Chemistry